Analysis of Hoax Exposure on TikTok Social Media among Islamic Journalism Students at UIN Mahmud Yunus Batusangkar - Shalma Saidah; Refika Mastanora (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This research is driven by the digital revolution, which has made TikTok a major source of information for young people. However, because of its personalized algorithm, TikTok has also become a platform for the widespread spread of hoaxes. The main goal of this study is to examine how exposure of Islamic journalism students at UIN Mahmud Yunus Batusangkar to hoaxes on TikTok affects public trust. These students were chosen as subjects because of their strategic significance as future journalists who hold journalistic ethics and tabayyun (verification) values. In-depth online interviews with students from the 2022–2025 cohorts and documentation in the form of screenshots of their TikTok activity were used to collect data for a descriptive qualitative research approach. The Miles and Huberman paradigm, which includes data reduction, data display, and conclusion drawing, was used to analyze the data. The findings show that exposure to TikTok hoaxes has a big impact on the cognitive, affective, and behavioral aspects of public trust. Students showed strong ability in recognizing false information on the cognitive level. This exposure caused negative emotions in the affective dimension, including disappointment and anger over poor-quality content. Students responded critically on the behavioral level by reporting content, offering instructional explanations in the comments section, and refraining from spreading false information. The study found that Islamic journalism students have good media literacy protection through active verification and healthy skepticism, even though the intensity of hoaxes on TikTok is very high.